2015
DOI: 10.1007/s11269-015-1001-3
|View full text |Cite
|
Sign up to set email alerts
|

Combining Stochastic Weather Generation and Ensemble Weather Forecasts for Short-Term Streamflow Prediction

Abstract: Ensemble streamflow predictions (ESPs) offer great potential benefits for water resource management, as they contain key probabilistic information for analyzing prediction uncertainty. Ensemble weather forecasts (EWFs) are usually incorporated into ESPs to provide climate information. However, there is no simple way to combine both of them, since EWFs are generally biased and under-dispersed. This study presents a new short-term (1 to 7 lead days) probabilistic streamflow prediction system combining stochastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…This approach represents a variant of post-processing bias-correction with the use of a stochastic weather generator and the change-factor method [43,44]. This method is efficient in generating weather timeseries for future projections, but constrained by the assumption that the weather cumulative distribution function retains properties of the historical dataset.…”
Section: Climate Data Processingmentioning
confidence: 99%
“…This approach represents a variant of post-processing bias-correction with the use of a stochastic weather generator and the change-factor method [43,44]. This method is efficient in generating weather timeseries for future projections, but constrained by the assumption that the weather cumulative distribution function retains properties of the historical dataset.…”
Section: Climate Data Processingmentioning
confidence: 99%
“…A number of research studies have been reported on hydrological forecasting in past decades, mainly including physical models and mathematical methods (X. L. Zhang, Peng, Zhang, & Wang, 2015). Physical models explore the hydrological dynamic process of watershed combing weather processes (Chen & Brissette, 2015;Smiatek, Kunstmann, & Werhahn, 2012;Ye et al, 2017), meteorological conditions (Hanna et al, 2013;Ralph, Coleman, Neiman, Zamora, & Dettinger, 2013) and underlying surface conditions (Rosenberg, Clark, Steinemann, & Lettenmaier, 2013;Sinha, Sankarasubramanian, & Mazrooei, 2014). However, due to the complexity of the hydrological processes affected by various factors such as runoff, rainfall and human activity, not only a large number of data and parameters are needed, but also it is difficult to obtain streamflow forecasting with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…applied GLUE (Generalized Likelihood Uncertainty Estimation) method to conduct multiple-scale uncertainty analysis and improved the sampling process [16] . Ye L et al used multiple-target optimization algorithm to construct the forecasting intervals of ensemble hydrological forecasting model [17] . By using atmosphere mode to do rainfall forecast and then applying rainfall runoff model to do runoff forecast can help achieve ensemble forecast.…”
Section: Introductionmentioning
confidence: 99%